PELATIHAN HIDROPONIK UNTUK MENINGKATKAN KETERAMPILAN ECOPRENEUR PADA MASA PENDEMIC COVID-19 - Muhammad Rapii; Isfi Sholihah; Agus Riswanto; Susilaswati Susilaswati (STIK KESETIAKAWANAN SOSIAL INDONESIA, 2022)
Environmental-based entrepreneurial skills (ecopreneur) need to be applied to all levels of society. Through hydroponic skills training activities involving Family Welfare Development women, apart from having a direct impact on reforestation in residential areas, it can also be a means of environment-based entrepreneurship and especially improve family food security during the Covid-19 pandemic. The reason for choosing the Family Welfare Development Agency in this neighborhood is that based on a survey, the housing location is in a densely populated area and has a narrow area of ​​land. Limited land results in the lack of greenery in the residential area. Whereas human resources in residential areas have the potential for considerable self-development as entrepreneurial agents, especially ecopreneurs. However, they lack knowledge and lack of training that encourages them to develop themselves. Therefore, this environment requires problem solving assistance in providing ecopreneur training media, the method of this service activity uses lecture methods, training and planting techniques as well as evaluating the effectiveness and efficiency of organic plant prototypes.